Tourism Destination Resilience against Global Geopolitical Crises: Extending Leiper's Tourism System Theory in an Era of High Volatility - Solahuddin Nasution; Gustanto Gustanto; Koko Sujatmoko; Fretika Putri (International Journal of Social Sciences and Humanities, 2026)
Global geopolitical crises  including armed conflicts, pandemic shocks, economic sanctions, and climate disasters  have exposed the structural fragility of tourism destination systems that evolved under conditions of relative stability. Leiper's (1979) foundational Tourism System model, while theoretically elegant in characterising the generating-transit-destination triad, was not designed to account for the cascading, non-linear disruptions that characterise the contemporary high-volatility environment. This study extends Leiper's framework by integrating a resilience layer  comprising adaptive governance capacity, system interconnection redundancy, and destination absorptive capacity  and empirically tests this extended model across six tourism destination clusters in North Sumatra Province, Indonesia. Drawing on a mixed-methods design (structured expert Delphi survey, n=48; stakeholder interviews, n=32; field observation), the study maps geopolitical vulnerability profiles and resilience trajectories for each cluster. Results reveal that destinations with higher adaptive governance capacity (notably the Samosir UNESCO Geopark cluster) demonstrate significantly stronger resilience trajectories post-crisis, while coastal clusters with low governance capacity show slow, incomplete recovery patterns. The Destination Resilience Index (DRI) developed in this study provides a replicable diagnostic and monitoring instrument for regional tourism governance bodies operating under conditions of chronic geopolitical uncertainty. The empirical analysis draws on data and literature current to 2026, reflecting the most recent developments in geopolitical volatility and destination resilience scholarship.